Analisa Tingkat Inflasi di Indonesia Menggunakan Metode Holt-Winters - Revi Rundupadang; Efraim Dudung Massora; Sri Yulianto Prasetyo (AITI, 2016)
This research aims to model the change in inflation rate in Indonesia. Inflation is defined as an increase in the price of goods or services that occur continuously. Ifthe known changes in a period of inflation it will be known the value of inflation in that period. Then from the model obtained, is expected to predict the value of inflation in Indonesia in the next period. By utilizing the data time series methods in use in this research is a method of Holt-Winters. Method of The Holt-Winters' (HW) smoothing is a generalization of the method of linear Holt. This technique was proposed in 1960 by Holt and Winters. This method is the development of a linear method of Holt. Holt-Winters method widely used in time series which shows a pattern of increase or decrease in the trend. By utilizing these methods shows that data prediction and the actual data is almost the same. From these data, there is a lower prediction datafrom actual data. Forecasting with Holt-Winters method can be said to be efficient ifat the time of the next level of inflation other than in the outermost color range class prediction.